Intradermal Delivery of Synthetic mRNA Using Hollow Microneedles for Efficient and Rapid Production of Exogenous Proteins in Skin - Sonia Golombek; Martin Pilz; Heidrun Steinle; Efrat Kochba; Yotam Levin; Dominique Lunter; Christian Schlensak; Hans Peter Wendel; Meltem Avci-Adali (Elsevier, 2018)
In recent years, synthetic mRNA-based applications to produce desired exogenous proteins in cells have been gaining importance. However, systemic delivery of synthetic mRNA can result in unspecific uptake into undesired cells or organs and, thereby, fail to target desired cells. Thus, local and targeted delivery of synthetic mRNA becomes increasingly important to reach the desired cell types and tissues. In this study, intradermal delivery of synthetic mRNA using a hollow microneedle injection-based method was evaluated. Furthermore, an ex vivo porcine skin model was established to analyze synthetic mRNA-mediated protein expression in the skin following intradermal delivery. Using this model, highly efficient delivery of synthetic mRNA was demonstrated, which resulted in detection of high levels of secretable humanized Gaussia luciferase (hGLuc) protein encoded by the microinjected synthetic mRNA. Interestingly, synthetic mRNA injected without transfection reagent was also able to enter the cells and resulted in protein expression. The established ex vivo porcine skin model can be used to evaluate the successful production of desired proteins after intradermal delivery of synthetic mRNAs before starting with in vivo experiments. Furthermore, the use of microneedles enables patient-friendly, painless, and efficient delivery of synthetic mRNAs into the dermis; thus, this method could be applied for local treatment of different skin diseases as well as for vaccination and immunotherapy.